FINANCIAL PLANNING AND FINANCING OF SPORTS COMPETITIONS - Srećko Novaković; Dragan Đuranović; Željko Vojinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Manager of sport competition has right to decide and also to take responsibility for costs, income and financial results. From economic point of wiev flexible budget and planning cost calculations is top management base for analyzing success level of sport competition. Flexible budget is made before sport competition with few output level, where one is always from static plan-master plan. At the end of competition when we have results, we make report of plan executing and we also analyzing plan variances. Results of comparation between achieved and planning level of static budget can be acceptable if achieved level is approximate to budget level or if we analyzing results from gross or net income. Flexible budget become very important in case of world economic crises.